The State-reinforced self-governance framework: conceptualizing and diagnosing legal and other institutional foundations of adaptive and transformative environmental governance - Daniel A. DeCaro; Edella C Schlager; Emmanuel Frimpong Boamah (Ecology and Society)
Governance of complex social-ecological dilemmas requires institutional innovation, adaptive decision making, and cooperation to address integrative, multi-scale problems. Governments can facilitate such adaptive and transformative governance (ATG) by enabling stakeholder capacity for self-organization and cooperation. However, the complexity of most governance systems makes it difficult to diagnose the ATG capacity of existing systems for institutional design. To address this gap, we introduce the State-reinforced self-governance (SRSG) framework, which builds upon Elinor Ostrom’s foundational frameworks for understanding institutional complexity in social-ecological systems. The SRSG framework introduces design principles, a typology of institutional capacities, and governance network approach to help analysts conceptualize and assess the adaptive/transformative capacity of governance systems. The framework also provides an updated conceptualization of State (government) action, facilitating assessment of de/centralization, co-production, and self-governance. We use case studies drawn from diverse systems and problems to illustrate key principles, including diverse roles and mechanisms governments use to enable or constrain ATG. Finally, we discuss how to analyze institutional evolution in terms of changes in underlying design principles (i.e., capacities), actor types, collectives, and governance network structures. We identify future research opportunities and challenges, and methodological advancements. Our goal is to provide analytical conventions that help scientists, policymakers, and dilemma stakeholders conceptualize and design more resilient and sustainable social-ecological systems.